Development of Galesong Beach Culinary Tourism Infrastructure based on Sustainability Aspects - Muhammad Syafri; Baharuddin Hamzah; Edward Syarif (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The culinary area of Galesong beach is located above the sea with a semi-permanent building structure where the existing infrastructure in the culinary tourism area currently does not meet the standards for infrastructure for a tourism area such as access to culinary tourism sites through dense residential areas with narrow roads for access to tourism areas. This study aims to explain the development of the culinary tourism infrastructure of the Galesong coast based on sustainability aspects. The research targets to explain the availability of infrastructure for handling development, analyze infrastructure needs, and analyze the direction of infrastructure development policies that support culinary tourism areas. This research uses the swot analysis method for infrastructure development strategy. The results of this study explain that the infrastructure in the Galesong beach culinary tourism area is available but has not met the standard norms, guidelines, and criteria. Culinary tourism areas need infrastructure to deal with coastal abrasion problems, fires, waste processing, drainage, and improvement of footpaths to culinary tourism areas. This research can be a reference for infrastructure development in the Galesong beach culinary area.